2016
DOI: 10.1007/s00125-016-3961-0
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study on microangiopathy in type 2 diabetic foot ulcer

Abstract: Aims/hypothesis We investigated the significance of microangiopathy in the development of foot ulcer, which is still disputed. Methods We assessed microangiopathy by histological analysis of the capillary ultrastructure using transmission electron microscopy and capillary density and arteriolar morphology in paraffin-embedded sections from the skin of type 2 diabetic patients: 30 neuroischaemic patients (Isc) revascularised with peripheral angioplasty and 30 neuropathic patients (Neu) with foot ulcer, compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 35 publications
3
26
0
9
Order By: Relevance
“…Overall, these findings suggest that PAD is more likely to be linked to diabetic microangiopathy than kidney failure in patients with type 2 diabetes. Of note, a recent histopathological study showed microangiopathic abnormalities in patients with type 2 diabetes who underwent amputation for ischemic diabetic foot (15). Urine ACR is now accepted as an independent cardiovascular risk factor in patients with and without type 2 diabetes (16).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these findings suggest that PAD is more likely to be linked to diabetic microangiopathy than kidney failure in patients with type 2 diabetes. Of note, a recent histopathological study showed microangiopathic abnormalities in patients with type 2 diabetes who underwent amputation for ischemic diabetic foot (15). Urine ACR is now accepted as an independent cardiovascular risk factor in patients with and without type 2 diabetes (16).…”
Section: Discussionmentioning
confidence: 99%
“…This delay was suggested to be due to a consequence of arteriolar occlusions which were commoner in the ischaemic patients and which correlated with a lower TcPO 2 that did improve after revascularization but remained still remained low when compared to neuropathic patients. However, this study did not include a control group of non‐diabetic patients with ischaemic ulceration where knowledge of their healing rates, frequency of arteriolar occlusion and TcPO 2 changes could be important before concluding that such differences are specific to the diabetic arteriolar occlusions …”
Section: Microvascular Dysfunction In the Diabetic Footmentioning
confidence: 99%
“…However, this study did not include a control group of non-diabetic patients with ischaemic ulceration where knowledge of their healing rates, frequency of arteriolar occlusion and TcPO 2 changes could be important before concluding that such differences are specific to the diabetic arteriolar occlusions. 33 Diabetic patients can have delayed healing of surgical wounds that appear to be related to poor glycaemic control and postoperative infection. There is some limited evidence that improving blood glucose levels in patients with type 1 diabetes is associated with an improvement of nailfold capillary (nutritive) blood flow, but if and to which extent these effects can be replicated in the diabetic foot remains to be determined.…”
Section: Diabetic Microangiopathy and Its Effect On Wound Healing Omentioning
confidence: 99%
“…In the UK Prospective Diabetes Study (UKPDS), age, A1C, systolic BP, high density lipoprotein cholesterol (HDL-C), previous CV disease and current smoking were found to be independent risk factors for PAD (53). In the BARI 2D trial, age, female sex, black African origin, smoking, pulse pressure, A1C and ACR were independent risk factors for PAD (54,55). The incidence rate of PAD was 3.5 times higher in BARI 2D than in ADVANCE, which may be explained by differences in each study's inclusion criteria and the definitions of PAD outcomes.…”
Section: Peripheral Vascular Diseasementioning
confidence: 99%